2020
DOI: 10.1177/0363546520904378
|View full text |Cite
|
Sign up to set email alerts
|

Superior Capsule Reconstruction for Irreparable Massive Rotator Cuff Tears: Does It Make Sense? A Systematic Review of Early Clinical Evidence

Abstract: Background: Treatment of irreparable massive rotator cuff tears (MRCTs) in patients without advanced glenohumeral osteoarthritis remains a challenge. Arthroscopic superior capsule reconstruction (SCR) represents a newer method for treatment with increasing popularity and acceptance. Purpose: To analyze the clinical evidence surrounding SCR and determine the current clinical outcomes postoperatively. Study Design: Systematic review. Methods: A systematic review of the literature was performed following the PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“… 114 Finally, SCR is a promising procedure that remains, however, relatively new and is subject to further research regarding optimal graft choice and surgical technique to avoid excessive strain on the construct during activities of daily living. 115 , 116 …”
Section: Rotator Cuffmentioning
confidence: 99%
“… 114 Finally, SCR is a promising procedure that remains, however, relatively new and is subject to further research regarding optimal graft choice and surgical technique to avoid excessive strain on the construct during activities of daily living. 115 , 116 …”
Section: Rotator Cuffmentioning
confidence: 99%
“…The current evidence suggests that for symptomatic cases of irreparable, massive RCTs, SCR is an alternative with good to excellent early clinical outcomes; however, long-term follow-up will determine the longevity and ultimate role of this method in the treatment of irreparable, massive RCTs. 70 SCR is performed in young patients with massive, irreparable posterosuperior RCTs with no arthritis and in patients with Goutallier fatty degeneration of stage 3 or higher with retraction of the supraspinatus or infraspinatus tendons going up to the glenoid or just medial to it. 71 It is contraindicated if a fixed high-riding humeral head is present.…”
Section: Superior Capsular Reconstructionmentioning
confidence: 99%
“…24 After Mihata et al 22 reported the clinical outcomes of 23 patients who underwent superior capsular reconstruction (SCR) using a fascia lata autograft, some authors reported favorable clinical outcomes of SCR. 1,6,12,16,17,21 In biomechanical studies, Mihata et al 23,25 also showed that SCR decreased superior migration of the humerus. Although cadaveric studies have demonstrated superior stability of the humerus, it remains unclear whether the humerus migrates superiorly after SCR in vivo.…”
mentioning
confidence: 99%